Unveiling the hidden connection: the blood-brain barrier’s role in epilepsy - Han, Jinkun; Wang, Ying; Wei, Penghu; Lu, Di; Shan, Yongzhi (Frontiers in Neurology, 2024)
Epilepsy is characterized by abnormal synchronous electrical activity of neurons in the brain. The blood-brain barrier, which is mainly composed of endothelial cells, pericytes, astrocytes and other cell types and is formed by connections between a variety of cells, is the key physiological structure connecting the blood and brain tissue and is critical for maintaining the microenvironment in the brain. Physiologically, the blood-brain barrier controls the microenvironment in the brain mainly by regulating the passage of various substances. Disruption of the blood-brain barrier and increased leakage of specific substances, which ultimately leading to weakened cell junctions and abnormal regulation of ion concentrations, have been observed during the development and progression of epilepsy in both clinical studies and animal models. In addition, disruption of the blood-brain barrier increases drug resistance through interference with drug trafficking mechanisms. The changes in the blood-brain barrier in epilepsy mainly affect molecular pathways associated with angiogenesis, inflammation, and oxidative stress. Further research on biomarkers is a promising direction for the development of new therapeutic strategies.